7 Steps to Transform Your Life Using NLP, Coaching & Hypnosis (Global Business Management Review (GBMR), 2022)
Joyce, H. Campbell, is a Hypnotherapist, a Master Practitioner of NLP, a Master Coach an MBTI practitioner and a trainer of NLP, Hypnotherapy and Coaching. She now trains people to be Hypnotherapists, NLP practitioners and Coaches and she continues to extend her services to the private and corporate clients. A Master Coach still passionate about what she does and her book “7 Steps to Transform Your Life Using NLP, Coaching & Hypnosis” brings some powerful psychological and coaching tools that she uses with her clients to a wider audience. This book is a real action oriented book and one which really does have the impact to help make significant changes in one’s life. The book inspires the reader to change their lives by following 7 simple steps. As an expert in the field, she has given great attention to detail, is thorough, kind and polite and is very passionate about what she does. She is very much considerate about her client’s requests and makes sure that they have happiness with everything throughout the project interaction phase. Her specialties include as an accredited trainer in NLP, Hypnotherapy, Coaching, Corporate Coaching, Team Development, MBTI Profiling, Small business development and also as an author.